INTEGRATING AI CHATBOTS FOR EMERGENCY COMMUNICATION IN TEACHING AND LEARNING IN UNIVERSITIES IN ANAMBRA STATE: A CASE STUDY OF CHUKWUEMEKA ODUMEGWU OJUKWU UNIVERSITY, IGBOARIAM (UNIZIK Journal of Educational Management and Policy, 2025)
The integration of Artificial Intelligence (AI) chatbots into emergency communication systems in higher education holds significant promise for enhancing safety and responsiveness in universities. This study investigates the application of AI chatbots for emergency communication within Chukwuemeka Odumegwu Ojukwu University (COOU) in Igboariam, Anambra State, Nigeria. As universities face various emergencies—including natural disasters, health crises, and security threats—the effectiveness of communication is critical. Traditional communication methods often fail to provide the immediate and clear information needed during such critical times. This research explores how AI chatbots can bridge this communication gap by offering real-time responses, disseminating important safety information, and guiding students and staff through emergencies. The study employs a mixed-methods approach, combining quantitative surveys and qualitative interviews with university stakeholders, including students, faculty, and administrative staff. Initial findings indicate that AI chatbots can significantly enhance emergency communication efficiency, improve stakeholder engagement, and foster a proactive culture of safety on campus. Additionally, insights into the potential challenges and barriers to chatbot implementation in the Nigerian educational context are discussed. Overall, this research contributes to the growing body of literature on AI applications in education and highlights the need for innovative communication strategies that support effective crisis management. The findings underscore the potential of AI chatbots to transform emergency communication practices in universities, ensuring that educational institutions can maintain safety and a conducive learning environment even during unforeseen crises. Future recommendations for implementing AI chatbots in emergency communication systems are also provided.
Keywords: Artificial Intelligence (AI), Chatbots, Emergency Communication and Student Safety